The Effect of Maryam Prenatal Exercise on Labor Duration: A Systematic Review - Neng Kurniati; Suharso Hadisaputro; Rr. Sri Endang Pujiastuti (Alta Dharma Publisher, 2020)
The Extension of labor duration is associated with increased morbidity and mortality. Prenatal exercises have proven a positive effect on labor but still very low level of effectiveness against the labor duration. Salat has proven a positive effect on fitness, healthy and has a rehabilitative effect. Maryam Prenatal is a modification of prenatal basic exercise with postural bowing, sitting and prostrating like salat in Islam with dzikr. This systematic review aims to assess the effect of Maryam Prenatal on the labor duration. The systematic literature search with study criteria that examined physical exercise and salat for labor or health was carried out on the Pubmed, ScienceDirect and researchgate databases. Study quality was assessed by a tool of standard quality assessment of the quantitative study (QATQS). This review received 4 intervention studies, 1 retrospective, and 4 observational studies. 5 articles showing positive results on reducing the labor duration and 4 articles on salat show positive results to the health. Our overall conclusion that the hypothesis of Maryam Prenatal positive effect on the labor duration with an increase in the effect size. Therefore, we recommend further research that considers the influence of Maryam Prenatal as new method pregnancy exercise on labor duration.